Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/mao.0000000000001059
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Smoking on Ossiculoplasty Outcomes

Abstract: Smoking is not a significant risk factor for anatomic failure of cartilage tympanic membrane graft or worsened audiometric outcome after ossiculoplasty. However, complications were significantly more common in smokers, supporting the practice of primary tympanostomy tube placement at the time of ossiculoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Smoking negatively affects outcomes in all surgical fields 1 . In otology specifically, smoking has a negative impact on outcomes, particularly in tympanoplasties 2–7 . When compared with nonsmokers, smokers have worse hearing outcomes, more grafts failures, and more extensive middle ear disease processes 3 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking negatively affects outcomes in all surgical fields 1 . In otology specifically, smoking has a negative impact on outcomes, particularly in tympanoplasties 2–7 . When compared with nonsmokers, smokers have worse hearing outcomes, more grafts failures, and more extensive middle ear disease processes 3 …”
mentioning
confidence: 99%
“…1 In otology specifically, smoking has a negative impact on outcomes, particularly in tympanoplasties. [2][3][4][5][6][7] When compared with nonsmokers, smokers have worse hearing outcomes, more grafts failures, and more extensive middle ear disease processes. 3 Cigarette smoking contributes to poorer outcomes by several mechanisms of action.…”
mentioning
confidence: 99%
“…Clinically, otolaryngologists are very familiar with the deleterious effects that smoke and tobacco can have on the upper airway. Within otology, the effects of tobacco and nicotine have also been well documented, though with varying conclusions as to the outcome consequences (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…and Becvarovski and Kartush. 8,16,24 Coelho and Peng found a greater proportion of smokers required revision surgery for persistent cholesteatoma, conductive hearing loss and tympanic membrane perforation compared with non-smokers ( n = 6 (13.3 per cent) and n = 4 (4.7 per cent), respectively). 21 In an assessment of 30-day post-operative outcomes following otological surgery, smokers have also been found to have increased odds of soft tissue complications including 89 per cent increased odds of superficial wound infections (95 per cent CI, 1.32–2.86) and almost 300 per cent increased odds of wound dehiscence (95 per cent CI, 1.26–11.60).…”
Section: Cigarettes and Middle-ear Disease And Surgerymentioning
confidence: 99%
“…Trialists with increased success rates amongst smokers have attributed this to use of cartilage grafts rather than temporalis fascia owing to its metabolic properties and resistance to retraction, atelectasis and perforation. 21,24,25 In one trial utilising both graft tissues, a 75 per cent failure was reported amongst smokers when temporalis fascia was used compared with similar success rates between smokers and non-smokers (88.9 per cent and 76.8 per cent, respectively) when cartilage grafts were used, further advocating the use of cartilage as routine in smokers. 19…”
Section: Cigarettes and Middle-ear Disease And Surgerymentioning
confidence: 99%